Non-invasive monitoring of pulmonary artery pressure from timing information by EIT: experimental evaluation during induced hypoxia. (20th May 2016) - Proença, Martin; Braun, Fabian; Solà, Josep; Adler, Andy; Lemay, Mathieu; Thiran, Jean-Philippe; Rimoldi, Stefano F
Abstract: Monitoring of pulmonary artery pressure (PAP) in pulmonary hypertensive patients is currently limited to invasive solutions. We investigate a novel non-invasive approach for continuous monitoring of PAP, based on electrical impedance tomography (EIT), a safe, low-cost and non-invasive imaging technology. EIT recordings were performed in three healthy subjects undergoing hypoxia-induced PAP variations. The pulmonary pulse arrival time (PAT), a timing parameter physiologically linked to the PAP, was automatically calculated from the EIT signals. Values were compared to systolic PAP values from Doppler echocardiography, and yielded strong correlation scores ( r = − 0.94 ± 0.07 ) for all three subjects. Results suggest the feasibility of non-invasive, unsupervised monitoring of PAP.